In Vitro Activities of 28 Antimicrobial Agents against Staphylococcus aureus Isolates from Tertiary-Care Hospitals in Korea: a Nationwide Survey - Kim, Hong Bin (American Society for Microbiology, 2004)
Staphylococcus aureus, one of the most frequently isolated pathogens in both hospitals and the community, has been particularly efficient at developing resistance to antimicrobial agents. As methicillin-resistant S. aureus (MRSA) has prevailed and, furthermore, as S. aureus with reduced susceptibility to vancomycin has emerged, the therapeutic options for the treatment of S. aureus infections have become limited. To update the current status of antibiotic resistance, clinical S. aureus isolates were collected from eight university-affiliated hospitals from June 1999 to January 2001. Susceptibility tests with 28 antibiotics were performed by the disk diffusion method. Among a total of 682 isolates, the methicillin resistance rate was 64% (439 of 682), and most of the MRSA isolates were resistant to multiple classes of antibiotics. Although a constitutive macrolide-lincosamide-streptogramin B resistance phenotype was common, no isolates were resistant to quinupristin-dalfopristin or linezolid. Rifampin, fusidic acid, trimethoprim-sulfamethoxazole, and arbekacin showed superior in vitro activity compared with the other antibiotics against the MRSA isolates. No isolates showed reduced susceptibility to vancomycin.